1990
DOI: 10.1039/c39900001258
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical reactions of 1,3-bis(diazo)indan-2-one in an argon matrix at 10 K

Abstract: Irradiation of 1,3-bis(diazo)indan-2-one (3) in an argon matrix a t 10 K afforded the diazo ketene (7) via the photolabile diazo ketocarbene (5), and further irradiation caused the decomposition of the second diazo group to give strained carbonyl compounds as final photoproducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…They have found that both provide a ketone that is tentatively assigned as 153, the only reported cumulenone in the cycloproparene series. [151][152][153] The existence of the transient cyclopropenone-fused heterocycle 154 was proposed by Reinecke 154 involvement of this ketone has been negated from use of matrix studies. Thus, Teles, Hess, and Schaad 155 have shown that the pseudocarbene ring opened form 155 of 154 is formed directly and that it is this species that is trapped.…”
Section: Oxocycloproparenes (Benzocyclopropenones)mentioning
confidence: 99%
See 1 more Smart Citation
“…They have found that both provide a ketone that is tentatively assigned as 153, the only reported cumulenone in the cycloproparene series. [151][152][153] The existence of the transient cyclopropenone-fused heterocycle 154 was proposed by Reinecke 154 involvement of this ketone has been negated from use of matrix studies. Thus, Teles, Hess, and Schaad 155 have shown that the pseudocarbene ring opened form 155 of 154 is formed directly and that it is this species that is trapped.…”
Section: Oxocycloproparenes (Benzocyclopropenones)mentioning
confidence: 99%
“…The group of Tomioka at Mie has also addressed the five- and six-membered bisdiazoketones, 151 and 152 . They have found that both provide a ketone that is tentatively assigned as 153 , the only reported cumulenone in the cycloproparene series. The existence of the transient cyclopropenone-fused heterocycle 154 was proposed by Reinecke from trapping experiments with hexa- and penta-fluoroacetone in 1980 (Scheme ). Much more recently, the involvement of this ketone has been negated from use of matrix studies.…”
Section: Oxocycloproparenes (Benzocyclopropenones)mentioning
confidence: 99%
“…The thermal oxygenation of 123 in 1 % (Vdoped Ar matrices at 35 K resulted in the formation of a carbonyl O-oxide, which was identified by its intense 0-0 stretching vibration at 970 and 945 cm-1. 209 A five-membered heterocyclic carbene is 2,3-dihydro-2-oxo-l-methyl-indol-3-ylidene (124), which was generated by irradiation of the corresponding diazo precursor and characterized by ESR spectroscopy. 211 In solution the carbene dimerizes to give isoindigo.…”
Section: Vinyl-and Ethynylcarbenesmentioning
confidence: 99%
“…The principal photoproducts of208 in Ar were acetyl chloride, ketene, and HC1, while in N2 traces of methyl chloride and CO were also observed. This is in contrast to the room temperature decomposition of the carbene which produces mainly methyl chloride and CO. More evidence for carbene 208 was provided by trapping experiments with HC1, which produced dichloromethyl methyl ether, and from the direct IR observation of the dimerization of 208 in MP glass at 80 K. Geometrical isomers, indicating significant double bond character for the C-0 bond, were also observed for methoxyfluorocarbene (209),377 phenoxychlorocarbene (210),378 and methylmethoxycarbene (211). 379 On further irradiation, these carbenes rearrange to the corresponding carbonyl compounds, accompanied by loss of CO and hydrogen halide.…”
Section: Oxycarbenesmentioning
confidence: 99%